ANALISIS YURIDIS PUTUSAN PENGADILAN NEGERI BLORA TENTANG DUALISME KEPENGURUSAN YAYASAN PENDIDIKAN ISLAM KARTAYUDA YANG AKTA PENDIRIANNYA DIBUAT OLEH DAN DIHADAPAN NOTARIS (Studi Kasus Putusan Perkara PN Blora No. 34/Pdt.G/2015/PN.Bla) - Muslim Ansori; Akhmad Khisni (Jurnal Akta, 2017)
With the enactment of the Education System Act no 20 of 2003 (better known as the Sisdiknas Act), the State has determined that educational institutions should have a legal umbrella in the form of a legal entity, or better known as the Legal Entity Education. As a non-profit organization, the Foundation is the right legal entity that becomes a place for educational institutions, especially private schools. Therefore, of course, Notary has a very crucial role in making notary deed in the form of establishment and deed of change, such as example how in making the right basic budget and not multi interpresatasi for stake holders in the foundation. Therefore, the role of function and authority of the organ of the foundation must be clearly stated in the articles of association, so as not to cause a dispute in the future.KEYWORDS: Notaries, Foundation, Organ Foundation,